KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA TANJUNG MEKAR KECAMATAN SAMBAS KABUPATEN SAMBAS - Azhar Azhar; Irfan Setiawan (Post Graduate School of Government Science, 2024)
Lack of persuasive relationship between the Village Head and the entire community in the village. This is what causes a lack of communication process between the village head and the community in planning and implementing village development. The leadership of the village head has a big role in determining the direction of policy in development in the village. This research aims to determine the leadership of the Tanjung Mekar Village Head in increasing community participation in village development. This research uses a descriptive method with a survey approach. The research sample included the Village Head, village officials and the community. Data was collected through interviews, questionnaires and observations. The research results show that the leadership of the Tanjung Mekar Village Head in increasing community participation in village development is classified as